2018
DOI: 10.1101/475723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The long noncoding RNAHand2asorchestrates heart development through regulation of precise expression ofHAND2

Abstract: 1Rigorous exploration and dissection of potential actions and effects of long noncoding RNA 2 (lncRNA) in animals remain challenging. Here using multiple knockout mouse models and single-alleles of Hand2as in mouse (Han et al., 2018). Full-length deletion of the entire Hand2as sequence 1 (Hand2as F/F KO) led to dysregulated cardiac gene expression programs, ventricular septal defects 2 and heart hypoplasia and perinatal death, reminiscent of congenital heart diseases. A short distal 3 deletion at the 3' end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Finally, the expression of HAND2 -critical for ventricular CMs expansion -is initially discovered in the cardiac crescent at E7.75 and will continue throughout the linear heart tube at E8.5. It has been recently shown that the lncRNA Uph (also named Hand2as or lncHand2), playing critical roles in the regulation of the precise expression of HAND2, together with miR-1-2 family in looping heart, to eventually lead to chamber formation [56,57].…”
Section: From Cardiac Crescent To Looping Heart Tube: the Role Of Ncrnasmentioning
confidence: 99%
“…Finally, the expression of HAND2 -critical for ventricular CMs expansion -is initially discovered in the cardiac crescent at E7.75 and will continue throughout the linear heart tube at E8.5. It has been recently shown that the lncRNA Uph (also named Hand2as or lncHand2), playing critical roles in the regulation of the precise expression of HAND2, together with miR-1-2 family in looping heart, to eventually lead to chamber formation [56,57].…”
Section: From Cardiac Crescent To Looping Heart Tube: the Role Of Ncrnasmentioning
confidence: 99%